No Functional Role for microRNA-342 in a Mouse Model of Pancreatic Acinar Carcinoma - Dooley, James; Lagou, Vasiliki; Pasciuto, Emanuela; Linterman, Michelle A.; Prosser, Haydn M.; Himmelreich, Uwe; Liston, Adrian (Frontiers in Oncology, 2017)
The intronic microRNA miR-342 has been proposed as a potent tumour-suppressor gene. miR-342 is found to be downregulated or epigenetically silenced in multiple different tumour sites, and this loss of expression permits the upregulation of several key oncogenic pathways. In several different cell lines, lower miR-342 expression results in enhanced proliferation and metastasis potential, both in vitro and in xenogenic transplant conditions. Here we sought to determine the function of miR-342 in an in vivo spontaneous cancer model, using the Ela1-TAg transgenic model of pancreatic acinar carcinoma. Through longitudinal magnetic resonance imaging monitoring of Ela1-TAg transgenic mice, either wildtype or knockout for miR-342, we found no role for miR-342 in the development, growth rate or pathogenicity of pancreatic acinar carcinoma. These results indicate the importance of assessing microRNA function in the complex physiology of in vivo model systems, and indicate that further functional testing of miR-342 is required before concluding it is a bona fide tumour-suppressor-miR.